PENINGKATAN KEMAMPUAN MENCERITAKAN KEMBALI ISI DONGENG DENGAN MENGGUNAKAN MODEL ROLE PLAYING PADA SISWA KELAS III SD INPRES OEPURA 2 - Amelia Sedo Barek, Maria; Robot, Marselus; Koro, Maxsel (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The results of research by Maria Amelia Sedo Barek, NIM 2201140165 Elementary School Teacher Education Study Program in 2006, entitled "Improving the Ability to Retell Fairy Tales Using Role-Playing Models for Grade III Students of SD Inpres Oepura 2 Kupang. Supervised by Dr. Drs. Maarselus Robot, M.Si and Maxsel Koro, S.Pd., M.Pd. ". This study aims to determine the improvement in student learning outcomes by using role-playing models in learning about Telling Fairy Tales to Improve Learning Outcomes of Grade III Students of SD Inpres Oepura 2. The focus of this study is to improve the ability to retell fairy tales using role-playing models. The type of research used is (PTK), which is carried out in several stages, namely: planning, implementation, observation, and reflection. Then, the subjects of the study were all 31 grade III elementary school students. The research instruments included learning outcome tests, observation sheets of teacher and student activities, and documentation. The results of the study indicate that 16 (51.61%) students achieved mastery in cycle 1, while 15 (48.39%) students did not reach the completion criteria (KKTP). However, after improvements were made to the learning process in cycle 2, there was a significant improvement, with an average score of 90.32% to 9.68%.  Based on the research problem formulation, it is concluded that role-playing, assisted by role-playing, is effective in improving the abilities of third-grade students at  SD Inpres Oepura 2, as evidenced by the increase in their ability to retell fairy tales from cycle 1 to cycle 2.